2016
DOI: 10.1016/j.watres.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Sludge bio-drying: Effective to reduce both antibiotic resistance genes and mobile genetic elements

Abstract: a b s t r a c tSewage sludge is considered as one of major contributors to the increased environmental burden of ARGs. Sludge bio-drying was increasingly adopted due to its faster sludge reduction compared with composting. The fate of ARGs during full-scale sludge bio-drying was investigated to determine whether it could effectively reduce ARGs, and the contributions of bacterial community, horizontal gene transfer (HGT) through mobile genetic elements (MGEs) and co-selection from heavy metals to ARGs profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…In particular, the abundances of tetL, sul2, strA, ermB, ISCR1 and intI1 were enriched by 9.5, 10.7, 10.7, 377.2, 69.4, and 48.0 times, respectively (Figure 1c). This result is in line with previous studies showing that abundances of tetL, sul2, ermB can be found in reasonably high abundances after composting (Qian et al, 2016;Zhang et al, 2016).…”
Section: Tracing Arg and Mge Abundances And Diversity Throughout Compsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, the abundances of tetL, sul2, strA, ermB, ISCR1 and intI1 were enriched by 9.5, 10.7, 10.7, 377.2, 69.4, and 48.0 times, respectively (Figure 1c). This result is in line with previous studies showing that abundances of tetL, sul2, ermB can be found in reasonably high abundances after composting (Qian et al, 2016;Zhang et al, 2016).…”
Section: Tracing Arg and Mge Abundances And Diversity Throughout Compsupporting
confidence: 93%
“…Therefore, we decided to study the abundance of these ARGs during FW composting by choosing ten tetracycline resistance genes (tetA, tetB, tetC, tetG, tetL, tetM, tetQ, tetO, tetW, and tetX), seven macrolide resistance genes (ermB, ermF, ermM, ermT, ermX, mefA, and ereA), seven aminoglycoside resistance genes (aacA4, aadA, aadB, aadE, aphA1, strA, and strB), and three sulfonamide resistance genes (sul1, sul2, and sul3) totaling 27 different ARGs. To investigate potential changes in the abundance of mobile genetic elements (MGEs), we measured abundances of two integrase genes (intI1, intI2), two plasmid genes (ISCR1, IncQ) and one transposon (Tn916/1545, abbreviated as Tn916) gene that have often been connected with the movement of ARGs in the environment (Ma et al, 2017;Zhang et al, 2016). The bacterial abundance was measured as 16S rRNA gene copy numbers using SYBR-Green qPCR.…”
Section: Measuring Changes In Arg and Mge Abundances With Quantitativmentioning
confidence: 99%
See 1 more Smart Citation
“…Sludge bio-drying of municipal biosolids effectively reduced levels of the 16S rRNA, intI1, sul1, and erm(B) genes by 0.3 to 0.99-log. 67 Similarly, composting of sewage sludge (20 -60°C) substantially reduced the erm(B) genes levels by 1.55log, but failed to reduce levels of the sul1 and intI1 genes. 68 Previous studies have suggested that more rigorous technologies such as biosolids incineration are zero-risk solutions for the reduction of ARGs, although there are trade-offs with air quality and the loss of value-added soil amendment products.…”
Section: Comparison Of Pyrolysis To Other Biosolids Handling Processementioning
confidence: 97%
“…Recent work has also demonstrated that HGT is promoted in subinhibitory concentrations of antibiotics [43] and that positive selection might even inhibit HGT by eliminating possible recipients in the environment [44]. However, the analysis of ARG transfer in WWTPs is seriously hindered by the lack of suitable methods for high-throughput assessment of ARG transfer under real WWTP conditions, so it is not surprising that there is a knowledge gap in our understanding of the transfer of ARGs in WWTPs [45,46].…”
Section: Transfer Of Antibiotic-resistance Genesmentioning
confidence: 99%